The Impact of China's WTO Accession on East Asia - Ianchovichina, Elena 2000- (The World Bank, 2003)
China's World Trade Organization (WTO) accession will have major implications for China and present both opportunities and challenges for East Asia. Ianchovichina and Walmsley assess the possible channels through which China's accession to the WTO could affect East Asia and quantify these effects using a dynamic computable general equilibrium model. China will be the biggest beneficiary of accession, followed by the industrial and newly industrializing economies (NIEs) in East Asia. But their benefits are small relative to the size of their economies and to the vigorous growth projected to occur in the region over the next 10 years. By contrast, developing countries in East Asia are expected to incur small declines in real GDP and welfare as a result of China's accession, mainly because with the elimination of quotas on Chinese textile and apparel exports to industrial countries China will become a formidable competitor in areas in which these countries have comparative advantage. With WTO accession China will increase its demand for petrochemicals, electronics, machinery, and equipment from Japan and the NIEs, and farm, timber, energy products, and other manufactures from the developing countries in East Asia. New foreign investment is likely to flow into these expanding sectors. The overall impact on foreign investment is likely to be positive in the NIEs, but negative for the less developed East Asian countries as a result of the contraction of these economies' textile and apparel sector. As China becomes a more efficient supplier of services or a more efficient producer of high-end manufactures, its comparative advantage will shift into higher-end products. This is good news for the poor developing economies in East Asia, but it implies that the impact of China's WTO accession on the NIEs may change to include heightened competition in global markets.